Vloga evropskih programov na področju mladine pri socialnem vključevanju mladih - Mayr, Mojca (Socialno delo, 2024)
By describing the content, structural and financial characteristics of European programmes in the field of youth and summarizing research and analyses of the effects of their implementation from 2019 to 2023, the authors justify the role of programmes in the social inclusion of young people. By enhancing the inclusion of young people with fewer opportunities and positive discrimination, European youth programmes ensure equal opportunities. Although young people with fewer opportunities enter programme activities with different starting points compared to their peers without limited access to opportunities, this does not lead to differences in learning outcomes. The authors deal with social and cultural capital, equity in education, the importance of non-formal education and the barriers of young people to participation in programmes.
Keywords: EU programmes; inclusive education; inkluzija; mladi; mladinsko delo; programi EU; social justice; socialna pravičnost; vključujoče izobraževanje; youth